Meet the Expert : Selected Experts on AI in Manufacturing - Armstrong, Scott; Armstrong, Scott; Patel, Suhas; Hassman, Jim; Borchers, Sebastian (O'Reilly Media, Inc., 2020)
Sponsored by Intel Join us for our Meet the Expert series from Intel. Each event will feature three to four short back-to-back presentations from Intel partners from industries including healthcare, banking and finance, retail, security, and more. Learn how companies are solving real-world business problems across a variety of AI workloads and how enterprise customers are using these solutions today. This event includes the following four brief talks: How to improve operations MFG through better asset performance Quality Optimization for Metal Processing Plants Rapid Enterprise-scale AI Acceleration for Manufacturing & Supply Chain nLine - Solving 360° Inline Quality Control at High-Speeds using SOTA AI technology.